The effect of Haemophilus influenzae type b and pneumococcal conjugate vaccines on childhood pneumonia incidence, severe morbidity and mortality - Theodoratou, Evropi (Oxford University Press, 2010)
Background With the aim of populating the Lives Saved Tool (LiST) with parameters of effectiveness of existing interventions, we conducted a systematic review of the literature assessing the effect of Haemophilus influenzae type b (Hib) and pneumococcal (PC) conjugate vaccines on incidence, severe morbidity and mortality from childhood pneumonia. Methods We summarized cluster randomized controlled trials (cRCTs) and case–control studies of Hib conjugate vaccines and RCTs of 9- and 11-valent PC conjugate vaccines conducted in developing countries across outcome measures using standard meta-analysis methods. We used a set of standardized rules developed for the purpose of populating the LiST tool with required parameters to promote comparability across reviews of interventions against the major causes of childhood mortality. The estimates could be adjusted further to account for factors such as PC vaccine serotype content, PC serotype distribution and human immunodeficiency virus prevalence but this was not included as part of the LiST model approach. Results The available evidence from published data points to a summary effect of the Hib conjugate vaccine on clinical pneumonia of 4%, on clinical severe pneumonia of 6% and on radiologically confirmed pneumonia of 18%. Respective effectiveness estimates for PC vaccines (all valent) on clinical pneumonia is 7%, clinical severe pneumonia is 7% and radiologically confirmed pneumonia is 26%. Conclusions The findings indicated that radiologically confirmed pneumonia, as a severe morbidity proxy for mortality, provided better estimates for the LiST model of effect of interventions on mortality reduction than did other outcomes evaluated. The LiST model will use this to estimate the pneumonia mortality reduction which might be observed when scaling up Hib and PC conjugate vaccination in the context of an overall package of child health interventions.